Application of Agro-industrial Solid Waste as Biochar for Iron (II) Removal from Aqueous Solution - Rusnam, Rusnam; Yanti, Nika Rahma; Puari, Aninda Tifani; Sari, Nurmala (The University of Lampung, 2024)
In recent years, various industrial activities have introduced a high concentration of iron in the waterbody which causes serious problem to environment. This paper proposed the application of Exhausted Coffee Husk (ECH) as the biosorbent (BS) for removing iron (Fe) (II) in the aqueous solution. The ECH was carbonized into biochar before performing biosorption of the heavy metal ion. The effect of carbonization temperature, time and rate on the performance of the ECH biochar for removing Fe (II) were evaluated. The percentage of removal efficiency (RE) and the capacity of biosorption (mg/g) were considered as the determining parameters. The pyrolysis temperature was varied in a range of 200-600 °C with 50 °C of interval, while the time was in between 1h – 3h with a n interval of 0.5 h, and the temperature gradient of 5 – 25°C/min. The results showed that the temperature had a significant effect on the properties of the ECH biochar as BS for Fe (II). The temperature of 550 °C, at 1.5 h of time and 25 °C/min was chosen as the suggested carbonization temperature of biochar from ECH for biosorption of Fe (II). Keywords: Agro-industrial solid waste, Biosorption, Carbonization, Exhausted coffee husk (ECH), Heavy metal.